Effect of Deccox® in a free-choice, grain-mineral mixture on performance of yearlings grazing native range - F.K. Brazle (Kansas Agricultural Experiment Station Research Reports, 1990)
Including Deccox® in a free-choice, intake-limiting, grain-mineral mixture tended to increase grazing stocker gains and substantially reduced the percentage of newly arrived cattle treated for sickness and the number of treatments required per animal.
Keywords: Cattlemen' s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Deccox®; Bulls; Native grass; Mineral; Health